Pengembangan Kue Tetu Berbadid Ubi Ungu (Ipomoea Batatas) Dengan Penambahan Tepung Kacang Hijau (Vigna Radiata) Sebagai Selingan Alternatif Ibu Hamil Kekurangan Energy Kronik (KEK) - Nurul Aulia Masdiana (Journal of Comprehensive Science, 2026)
Chronic Energy Deficiency (CED) among pregnant women remains a major nutritional problem that may increase the risk of pregnancy complications and impaired fetal growth. One approach to addressing this issue is the development of locally based supplementary foods with adequate energy and nutritional content. This study aimed to develop tetu cake based on purple sweet potato (Ipomoea batatas) supplemented with mung bean flour (Vigna radiata) and to evaluate its sensory characteristics and nutritional potential as an alternative snack for pregnant women with CED. This research employed an experimental method using a Completely Randomized Design (CRD) consisting of three formulations with different proportions of purple sweet potato and mung bean flour. The product acceptance test was conducted using a hedonic test involving 50 semi-trained panelists, assessing color, aroma, taste, and texture attributes. Data were analyzed using the Kruskal-Wallis test and continued with the Mann-Whitney test when significant differences were identified. The results showed significant differences among formulations in all sensory attributes (p<0.05). Formula F1 obtained the highest acceptance score with a total value of 764 based on the frequency-weight method, while F2 demonstrated higher nutritional content, providing 152.5 kcal of energy and 2.9 grams of protein per serving. In conclusion, purple sweet potato-based tetu cake with mung bean flour supplementation has potential as an alternative supplementary food for pregnant women with CED. Further optimization is required to improve protein content and enhance its nutritional contribution.